A prospective randomized longitudinal study involving 6 months of endurance or resistance exercise. Conduit artery adaptation in humans - Spence, Angela; Carter, H.; Naylor, L.; Green, D. (Wiley-Blackwell Publishing Ltd., 2013)
This randomized trial evaluated the impact of different exercise training modalities on the function and size of conduit arteries in healthy volunteers. Young (27 ± 5 years) healthy male subjects were randomized to undertake 6 months of either endurance training (ET; n= 10) or resistance training (RT; n= 13). High-resolution ultrasound was used to determine brachial, femoral and carotid artery diameter and wall thickness (IMT) and femoral and brachial flow-mediated dilatation (FMD) and glyceryl trinitrate (GTN)-mediated dilatation. Improvements in peak oxygen uptake occurred with ET (from 3.6 ± 0.7 to 3.8 ± 0.6 l min−1, P= 0.024) but not RT. Upper body muscular strength increased following RT (from 57.8 ± 17.7 to 69.0 ± 19.5 kg, P < 0.001), but not ET. Both groups exhibited increases in lean body mass (ΔET, 1.4 ± 1.8 kg and ΔRT, 2.3 ± 1.3 kg, P < 0.05). Resistance training increased brachial artery resting diameter (from 3.8 ± 0.5 to 4.1 ± 0.4 mm, P < 0.05), peak FMD diameter (+0.2 ± 0.2 mm, P < 0.05) and GTN-mediated diameter (+0.3 ± 0.3 mm, P < 0.01), as well as brachial FMD (from 5.1 ± 2.2 to 7.0 ± 3.9%, P < 0.05). No improvements in any brachial parameters were observed following ET.Conversely, ET increased femoral artery resting diameter (from 6.2 ± 0.7 to 6.4 ± 0.6 mm, P < 0.05), peak FMD diameter (+0.4 ± 0.4 mm, P < 0.05) and GTN-induced diameter (+0.3 ± 0.3 mm, P < 0.05), as well as femoral FMD-to-GTN ratio (from 0.6 ± 0.3 to 1.1 ± 0.8, P < 0.05). Resistance training did not induce changes in femoral artery parameters. Carotid artery IMT decreased in response to both forms of training. These findings indicate that 6 months of supervised exercise training induced changes in brachial and femoral artery size and function and decreased carotid artery IMT. These impacts of both RT and ET would be expected to translate to decreased cardiovascular risk.